Testing of archaeological survey at peat extraction sites at Southern Lake Saimaa, South-East Finland - Koivisto Satu (Suomen arkeologinen seura, 2025)
Peatlands constitute central habitats for the occurrence of wetland archaeological sites. Consisting of waterlogged organic soils, they also provide advantageous conditions for the preservation of organic materials. The economic utilisation of peatlands has been extensive and long-lasting in mire-rich Finland. Archaeologists urgently seek to develop viable techniques for detecting, monitoring, and studying peatland archaeological sites, before they are deteriorated. One option is to conduct fieldwalking at commercial peat extraction sites, which was opportunistically tested in the detection of Mesolithic sites at southern Lake Saimaa by the University of Helsinki in 2015. In this paper, the main observations and challenges of the survey are reviewed and suggestions for further testing are presented.
Oodeja Mikalle - Odes to Mika - Оды Мике: Festschrift for Professor Mika Lavento on the occasion of his 60th birthday